A segregação por gênero no mercado de trabalho nos Estados de São Paulo e Pernambuco - Ana Maria Holland Ometto; Rodolfo Hoffmann; Marcelo Corrêa Alves (Economia Aplicada, 1997)
This study analyses the evolution of the occupational sex segregation and of the discrimination which harms the female worker in the states of Sao Paulo and Pernambuco, in the period 1981-1990. The source data is provided by National Household Sample Surveys (PNAD). The index ofsegregation developed by Duncan & Duncan (1955) indicates the existence of a considerable occupational segregation by gender in both states. Moreover, it shows that the degree of segregation decreases in Sao Paulo, but it increases considerably in Pernambuco. Earning equations are estimated including dummies for gender and for gender composition of occupations as explanatory variables. The results show that men earn more than woman and workers in male occupations earn more tham workers in female or integrated occupations.